Comparison of the stability of three fixation techniques between porous metal acetabular components and augments - Beckmann, Nicholas A.; Bitsch, Rudi G.; Jäger, Sebastian (Bone & joint research, 2018)
Objectives: In order to address acetabular defects, porous metal revision acetabular components and augments have been developed, which require fixation to each other. The fixation technique that results in the smallest relative movement between the components, as well as its influence on the primary stability with the host bone, have not previously been determined. Methods: A total of 18 composite hemipelvises with a Paprosky IIB defect were implanted using a porous titanium 56 mm multihole acetabular component and 1 cm augment. Each acetabular component and augment was affixed to the bone using two screws, while the method of fixation between the acetabular component and augment varied for the three groups of six hemipelvises: group S, screw fixation only; group SC, screw plus cement fixation; group C, cement fixation only. The implanted hemipelvises were cyclically loaded to three different loading maxima (0.5 kN, 0.9 kN, and 1.8 kN). Results: Screw fixation alone resulted in up to three times more movement (p = 0.006), especially when load was increased to 100% (p < 0.001), than with the other two fixation methods (C and SC). No significant difference was noted when a screw was added to the cement fixation. Increased load resulted in increased relative movement between the interfaces in all fixation methods (p < 0.001). Conclusion: Cement fixation between a porous titanium acetabular component and augment is associated with less relative movement than screw fixation alone for all implant interfaces, particularly with increasing loads. Adding a screw to the cement fixation did not offer any significant advantage. These results also show that the stability of the tested acetabular component/augment interface affects the stability of the construct that is affixed to the bone.Cite this article: N. A. Beckmann, R. G. Bitsch, M. Gondan, M. Schonhoff, S. Jaeger. Comparison of the stability of three fixation techniques between porous metal acetabular components and augments.
Gesehen am 23.04.2018